Predictors of response to insulin therapy in youth with poorly‐controlled type 2 diabetes in the TODAY trial. Issue 7 (27th August 2019) - Bacha, Fida; El ghormli, Laure; Arslanian, Silva; Zeitler, Philip; Laffel, Lori M.; Levitt Katz, Lorraine E.; Gandica, Rachelle; Chang, Nancy T.; Sprague, Jennifer E.; Macleish, Sarah A.; ,
Abstract: Objective: To understand the factors associated with glycemic control after starting insulin in youth with type 2 diabetes following glycemic failure (persistent HbA1c ≥8%) with metformin alone, metformin + rosiglitazone or metformin + lifestyle in the TODAY study. Methods: Change in HbA1c after add‐on insulin therapy and the factors predictive of glycemic response were evaluated. At 1‐year postinsulin initiation, 253 youth had a mean of 3.9 ± 1.0 visits since the time of insulin initiation. Participants were divided into three groups according to glycemic control: consistent decrease in HbA1c by ≥0.5%, change <0.5%, or consistent increase in HbA1c ≥0.5%, at 75% or more of the visits. Results: Within 1‐year postinsulin initiation, 33.2% of participants had a consistent HbA1c decrease of ≥0.5%, 46.2% changed HbA1c <0.5%, and 20.6% had an increase ≥0.5%. At randomization into TODAY and at time of insulin initiation, the three glycemia groups were similar in age, sex, race‐ethnicity, pubertal stage, BMI z‐score, diabetes duration, and insulin secretion indices. Consistent HbA1c improvement was associated with higher insulin sensitivity (1/fasting insulin) at randomization and at time of failure, higher adiponectin at randomization, and was not associated with indices of β‐cell function. Conclusions: Response to add‐on insulin was highly variable among youth in TODAY. Greater insulin sensitivity and higher adiponectin concentrations at randomization were associated with improved glycemic control after initiation of insulin. Due to limited information on adherence to insulin injections, the roles of adherence to the prescribed insulin regimen or psychosocial factors are unknown.